‘Desiccation tolerance of Rhamnidium elaeocarpum Reissek (Rhamnaceae) seeds - Lílian Abadia da Silva; Juliana de Fátima Sales; João Almir Oliveira; Édila Vilela de Resende Von Pinho; Heloisa Oliveira dos Santos; Marcos Antônio Soares (Acta Scientiarum. Agronomy, 2015)
This study aimed to investigate the desiccation tolerance of Rhamnidium elaeocarpum Reissek seeds through physiological and biochemical alterations. Fruit were collected from the municipality of Jaupaci, Goias State, Brazil, when the water content of their seeds had a 37% wet basis (w.b.) and the seeds were subsequently kept in a drying oven with air circulation at a temperature of 35ºC until a water content was reached of 20 to 12% (w.b.). The following parameters were evaluated: germination, germination speed index, emergence, emergence speed index, electrical conductivity and respiration rate. Furthermore, the electrophoretic profile of the isoenzymes: catalase, peroxidase and esterase, the enzymatic activities of endo-β-mannanase and α-amylase and the electrophoretic analysis of heat-resistant proteins were performed. A higher germination speed and respiratory rate was obtained for seeds with a water content of 12% w.b., and the activity of catalase isoforms was more pronounced in seeds with a higher degree of dehydration, which was in contrast to peroxidase, showed decreased activity. The seeds contained heat-resistant proteins of low molecular weight that ranged from 48.7 to 13.2 kDa. We found that the acquisition of drying tolerance in R. Elaeocarpum Reissek seeds is associated more with catalase than with esterase and peroxidase.